Perancangan Prototipe Sistem Kontrol Pintu Air Irigasi Berbasis Android dan Jaringan Nirkabel - Ahmad, Ramli; Mahpuz, Mahpuz (Infotek : Jurnal Informatika dan Teknologi, 2018)
Prototype of irrigation-based sluice control devices for Android and wireless networks has a long-term goal, namely how in the future there is an application or tool that is able to assist irrigation water distribution officers in controlling the floodgates remotely, so it is expected that with the help of these tools or technology officers can work faster and more efficient.In this study the manufacturing stage is divided into two, namely the manufacture of hardware and software making where the research starts from the collection of materials and tools, then the manufacturing stage is the design of tools in the form of sluice controllers and software design consists of two parts, namely in the control section which is a program android and on the receiver and executor section which is a microcontroller program. The next step is the assembly or making of a tool, the sluice controller. After the android and the floodgates controllers are finished, the testing phase will be carried out, which is to test whether the tools work as expected if there is an error to be evaluated so that later the tools will be made as expected, namely Android-based irrigation gates and wireless networksDOI : 10.29408/jit.v1i2.905